Interrelationship Among Business Units and Private University Performance: A Conceptual Framework - Siti Samsiah; Zul Azmi; Linda Hetri Suriyanti; Nik Maheran Bint Nik Muhammad (Fakultas Ekonomi Universitas Kadiri, 2022)
Knowing the performance of an organization is very important for the organization to know the achievements that have been planned. This also applies to organizations such as universities. The existence of higher education as a producer of intellectual human resources is very important as a benchmark for the progress of a nation. The purpose of this conceptual framework is to determine the relationship between the concept of the interrelationship among business units and the performance of tertiary institutions in the Indonesian context. In this study, the dimensions of tangible assets, intangible assets, and customer contact are used to measure the relationships between business units, while the dimensions of financial performance and non-financial performance are used to measure university performance. The unit of analysis in this research is the leadership at a private university in Pekanbaru City with the Dean, head of the department, Head of the Study Program, and secretary of the study program as respondents. The conceptual framework development is expected to become the next research literature to examine the relationship between units and higher education performance.